The relevance of a multidomain geriatric assessment in older patients with heart failure - Emma E.F. Kleipool; Julia H.I. Wiersinga; Marijke C. Trappenburg; Albert C. vanRossum; Carmen S. vanDam; Su‐San Liem; Mike J.L. Peters; M. Louis Handoko; Majon Muller (ESC Heart Failure)
Abstract Aims Physical frailty screening is more commonly performed at outpatient heart failure (HF) clinics. However, this does not incorporate other common geriatric domains. This study assesses whether a multidomain geriatric assessment, in comparison with HF severity or physical frailty, is associated with short‐term adverse outcomes. Methods and results This is a prospective cohort study of 197 patients with HF (mean age 78, 44% female) attending outpatient HF clinics. HF severity was assessed with New York Heart Association class (I‐II versus III‐IV) and N‐terminal pro b‐type natriuretic peptide levels. Physical frailty was assessed with the Fried frailty criteria (not frail, pre‐frail, and frail). The following geriatric domains were assessed: physical function, nutrition, polypharmacy, cognition, and dependency in activities of daily living. Logistic regression analyses adjusted for age, sex, diabetes and kidney function assessed 3 month risk of adverse health outcomes (emergency department visits, hospital admissions, and/or death) according to HF severity, physical frailty, and number of affected domains. Number (%) of patients with HF with no, 1, 2, and ≥3 domains affected were 36 (18%), 61 (31%), 58 (29%), and 42 (21%). Seventy‐four adverse outcomes were experienced in 50 patients at follow‐up. Severity of HF and physical frailty were not significantly associated with an increased risk of adverse health outcomes. However, increasing number of affected domains were significantly associated with an increased risk of adverse outcomes. Compared with no domains affected, odds ratios (95% confidence interval) for 1, 2, and ≥3 domains were 1.8 (0.5–6.5), 4.5 (1.3–15.4), and 7.2 (2.0–26.3) (P‐trend <0.01). Further adjustment for HF severity and frailty status slightly attenuated the effect estimates (P‐trend 0.02). Conclusions Having limitations in multiple domains appears more strongly associated with short‐term adverse outcomes than HF severity and physical frailty. This may illustrate the potential added value of a multidomain geriatric assessment in the evaluation and treatment of patients with HF with respect to relevant short‐term health outcomes.